Relational Factors Influencing Parents' Engagement in Special Education for High School Youth With Emotional/Behavioral Problems. (February 2020) - Carlson, Ryan G.; Hock, Robert; George, Melissa; Kumpiene, Gerda; Yell, Mitch; McCartney, Esther D.; Riddle, David; Weist, Mark D.
This study examined the relational factors influencing school engagement for parents of high school youth with emotional/behavioral disorders. Fourteen parents of high school students (12 mothers, two fathers) who received special education services participated in semistructured interviews. Formal qualitative analyses of audiotaped phone interviews revealed some positive and some negative experiences by parents, the importance of coparenting to increase supportiveness to their child (and dimensions of effective coparenting), and recommendations from them for improving family engagement processes. In general, parents appreciated and recommended proactive and positive communication and collaboration with school staff emphasizing student strengths, being genuinely and meaningfully involved in the Individualized Education Program (IEP) process, with adequate time allowed for this involvement, and for staff to be organized and engaged in working with them. Findings are discussed in relation to ideas for practice and policy enhancement, and future research directions.